A legal checklist for O.R. supervisors - Rozovsky, Lorne; Rozovsky, Fay (Operating Room Nurses Association of Canada Journal, 1988)
Legal problems can and should be avoided. This is especially true in hospitals and particularly true in the operating room. As the chief administrative ofﬁcer of the surgical plant, the responsibility for preventive law rests primarily on the shoulders of the operating room supervisor.